A mixed-methods validation of the Intuitive Eating Scale-2 for use with kidney transplant recipients - Rebecca J. Linnett; Stephanie J. Hubbard; Noelle Robertson; John Maltby (PLoS ONE, 2026)
Chronic kidney disease (CKD) affects approximately 850 million people worldwide, imposing not only substantial health burdens but also complex dietary management challenges. For kidney transplant recipients (KTRs), dietary restrictions often lessen post-transplant, yet the transition to a ‘normal’ diet is fraught with difficulty after years of externally imposed rules. In this context, intuitive eating, which emphasises internal hunger and satiety cues over external dietary mandates, may support the development of sustainable, self-managed eating behaviours. Despite the recent publication of a third version of the scale, the Intuitive Eating Scale-2 (IES-2) is currently the most widely-used measure of intuitive eating, but it has not yet been validated for use with KTRs. To address this gap, a mixed-methods validation study was conducted, integrating qualitative thinkaloud interviews with KTRs and a quantitative survey involving KTRs and a non-CKD comparison group, to evaluate the face, factorial and construct validity and internal consistency of the IES-2 within this population. Results from both qualitative and quantitative workstreams revealed critical psychometric and conceptual issues with the ‘Unconditional Permission to Eat’ (UPE) subscale, including compromised item discrimination, construct validity, and reliability, as well as responses being systematically influenced by participants’ experiences as KTRs. The original four-factor structure of the IES-2 was unsupported in both groups. Alternative models were tested, and an 11-item, three-factor structure excluding the UPE subscale demonstrated excellent fit across KTR and comparison samples. Although a third version of this scale now exists, there is no validation data available for people with kidney disease or solid organ transplantation, meaning these findings provide the first validated, contextually appropriate configuration of a scale of intuitive eating for use with KTRs, offering a robust tool to advance research and clinical practice in this population.